Application of Intelligent Management Model Based on Electronic Patient-Reported Outcome During Immunotherapy in Patients with Gastric Cancer: A Single-Center Retrospective Study - Li, Cuizhen; Wu, Danna (British journal of hospital medicine (London, England : 2005), 2024)
Gastric cancer is the third leading cause of cancer-related death worldwide, which seriously affects the health of patients. Immunotherapy is a commonly used clinical treatment for gastric cancer, but the adverse events caused by it seriously affect the prognosis of patients. Therefore, it is necessary to control and manage the disease risk of patients during immunotherapy. To explore the effect of applying an intelligent management model based on electronic patient-reported outcome (ePRO) in patients with gastric cancer during immunotherapy. The clinical data of 184 gastric cancer patients receiving immunotherapy in The Fourth Hospital of Hebei Medical University from September 2021 to September 2023 were retrospectively analyzed. Ninety patients receiving ePRO-based intelligent management were selected, and 85 patients were included in the observation group after excluding 5 patients. For the reference group, 94 patients receiving common case management were selected, with 90 patients being included after excluding 4 patients. After 6 months of follow-up, the nutritional status score, quality of life, treatment compliance and adverse events were compared between the two groups. No significant difference was detected in nutritional status and World Health Organization Quality of Life-BREF (WHOQOL-BREF) scores of the patients before discharge ( > 0.05). After 2 months of follow-up, compared with the reference group, the observation group had a higher proportion of patients in grade A and grade B, which was not statistically significant ( > 0.05), and significantly higher physiological and psychological scores ( < 0.001), but showed no meaningful differences in other fields ( > 0.05). After 4 months of follow-up, the nutritional status in the observation group was significantly improved ( < 0.05), and the subjects displayed higher WHOQOL-BREF scores ( < 0.05) than those in the reference group. No significant difference in the incidence of adverse events was detected ( > 0.05). After 6 months of follow-up, the treatment compliance of the observation group was 83.53%, which was significantly higher than that of the reference group (70.00%; < 0.05). The intelligent management model based on ePRO is conducive to improving the nutritional status of patients with gastric cancer during immunotherapy, as well as enhancing their quality of life and treatment compliance, making it worthy of clinical application.